2011
DOI: 10.1590/s1807-59322011000300021
|View full text |Cite
|
Sign up to set email alerts
|

An experimental model to study the effects of a senna extract on the blood constituent labeling and biodistribution of a radiopharmaceutical in rats

Abstract: Cassia angustifolia Vahl (senna) is a natural product that contains sennosides, which are active components that affect the intestinal tract and induce diarrhea. Authors have shown that senna produces DNA (deoxyribonucleic acid) lesions in Escherichia coli cultures and can act as an antifungal agent. Natural drugs can alter the labeling of blood constituents with technetium-99m (99mTc) and can affect the biodistribution of radiopharmaceuticals. In this work, we have evaluated the influence of a senna extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Uncaria tomentosa extract altered the uptake of the Na 99m TcO 4 in the heart, pancreas and muscle after the treatment orally (Moreno et al, 2007b). Souza et al (2011) demonstrated that natural products such as senna extracts can also induce changes in the biodistribution of Na 99m TcO 4. Jankovic and Djokic (2005) reported the alteration of the organ uptake of several radiobiocomplexes labeled with 99m Tc induced by the administration of the cytotoxic drugs methotrexate sodium and cyclophosphamide using this same experimental model (Jankovic and Djokic et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Uncaria tomentosa extract altered the uptake of the Na 99m TcO 4 in the heart, pancreas and muscle after the treatment orally (Moreno et al, 2007b). Souza et al (2011) demonstrated that natural products such as senna extracts can also induce changes in the biodistribution of Na 99m TcO 4. Jankovic and Djokic (2005) reported the alteration of the organ uptake of several radiobiocomplexes labeled with 99m Tc induced by the administration of the cytotoxic drugs methotrexate sodium and cyclophosphamide using this same experimental model (Jankovic and Djokic et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…The possible explanation to the appearance of drug interaction with radiopharmaceuticals are (i) modification of the radiopharmaceuticals, (ii) alteration of the labeling efficiency of the radiopharmaceuticals, (iii) modification of the target organ, (iv) modification of no target organ, and/or the (v) alteration of the biding of the radiopharmaceuticals with the blood proteins. [19] Thus, the development of biological models to study the drug interactions with radiopharmaceuticals is highly relevant. Our findings demonstrated the relevance of these experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…[1617] It has already been reported that biodistribution of radiopharmaceuticals and radiolabeling process can be modified by a wide variety of conditions, such as, drug therapy, radiation therapy, disease and medicinal plants therapy. [1819]…”
Section: Introductionmentioning
confidence: 99%
“…Data have demonstrated the effects of synthetic and natural drugs on this radiolabeling process (Mousinho et al, 2008;Holanda et al, 2009;Bustani et al, 2009;Rocha et al, 2009;De et al, 2009;Cekic et al, 2011;Souza et al, 2011). In consequence, the labeling of blood constituents with 99m Tc has been used as an in vitro assay to screening effects of synthetic or natural products that could have actions related to the band-3 and calcium channels or antioxidant/oxidant properties.…”
Section: +2mentioning
confidence: 99%